2005
DOI: 10.2527/2005.83122806x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pasteurization of potato slurry by-product fed in corn-or barley-based beef finishing diets1

Abstract: Pasteurization of vegetable by-products such as potato slurry (PS) before feeding may be necessary to prevent the spread of pathogens and beef carcass blemishes. We hypothesized that pasteurization would increase ruminal fermentability of PS starch. Four ruminally cannulated crossbred beef steers (initial BW = 432) were used in a 4 x 4 Latin square experiment with a 2 x 2 factorial arrangement of treatments to examine the main effects and interactions of pasteurization (54.4 degrees C for 2 h) of PS and grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Monteils et al (2002) reported in sacco potato peel starch disappearance rate was 5%/h compared with 34%/h for wheat starch. In contrast, Szasz et al (2005) reported that ensiled potato slurry starch was 27 to 38% soluble, and the insoluble fraction disappeared in vitro at 14%/h regardless of pasteurization at 54°C. This slurry probably was mostly peels and cooked coproduct based on chemical composition, in which most of the starch would have been gelatinized.…”
Section: Potato Starchmentioning
confidence: 89%
“…Monteils et al (2002) reported in sacco potato peel starch disappearance rate was 5%/h compared with 34%/h for wheat starch. In contrast, Szasz et al (2005) reported that ensiled potato slurry starch was 27 to 38% soluble, and the insoluble fraction disappeared in vitro at 14%/h regardless of pasteurization at 54°C. This slurry probably was mostly peels and cooked coproduct based on chemical composition, in which most of the starch would have been gelatinized.…”
Section: Potato Starchmentioning
confidence: 89%
“…Experimental procedures involving animals were approved by the University of Idaho Institutional Animal Care and Use Committee. Six ruminally and duodenally cannulated Angus-Jersey crossbred steers (450 kg of BW), which had been used in a previous study (Szasz et al, 2005), were fed the 6 test grains to examine the effects of kernel vitreousness and moisture at harvest on intake and digestibility of high-moisture corn. Steers were housed in individual pens (approximately 25 m 2 ) and had free choice access to fresh water.…”
Section: Metabolism Studymentioning
confidence: 99%
“…where a, b, and c = constants from the nonlinear model described previously, whereas k = fractional ruminal outflow rate that was assumed to be 5.0%/h (Orskov and McDonald, 1979). A 5.0%/h outflow rate has been used to estimate effective degradability of feedstuffs in previous trials (Hristov and McAllister, 2002;Szasz et al, 2005). Response variables were analyzed as a 6 × 6 Latin square with a 2 × 3 factorial arrangement using the MIXED procedure.…”
Section: Computations and Statistical Analyses All Datamentioning
confidence: 99%
“…Six zero-hour (T0) flask containing 1 g of grain sample and 100 ml of Kansas State pH 6.8 buffer solution (Marten and Barnes, 1980) followed by 15 min of incubation at 39˚C (Szasz et al, 2005) were included per run. T0 starch and DM disappearance were used to calculate the readily digestible fraction that disappears from the media before microbial fermentation (Ørskov et al, 1980).…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…In vitro starch (IVSD) and DM disappearance (IVDMD) for each sample were calculated as the amount of starch and DM that disappeared during the in vitro incubation and were fitted to the non-linear kinetic model (Ørskov and McDonald, 1979;Szasz et al, 2005) [-ct] ) where p is the starch or DM that disappeared at incubation time t (h); a is the soluble and rapidly degradable fraction (%); b is the potentially degradable fraction (%); c is the fractional rate at which b disappeared per hour. The effective DM and starch degradability (ED) were determined as per (Szasz et al, 2005;Anele et al, 2015); ED = a+ bc/(c+k)' where, a, b, and c are the constants obtained from the non-linear model, and k is the fractional outflow rate, assuming a medium passage rate of rumen solids outflow (5.0% h -1 ).…”
Section: In Vitro Experimentsmentioning
confidence: 99%